Subclinical myocardial dysfunction assessed by cardiac magnetic resonance feature tracking predicts ventricular arrhythmias in early-stage hypertension - Fang, Bin; Liao, Weiwei; Zhong, Jianping; Zhong, Junyuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSubstantial evidence supports the utility of cardiac magnetic resonance feature tracking (CMR-FT) in evaluating subclinical cardiac dysfunction. This study investigated the clinical value of CMR-derived left ventricular (LV) strain for detecting myocardial impairment in asymptomatic patients with hypertension (HTN) and explored its association with ventricular arrhythmias (VA).MethodsA retrospective analysis included 150 HTN patients [with/without LV hypertrophy (LVH)] and 60 healthy controls. Clinical data and CMR parameters were collected. Conventional LV functional indices and strain parameters—global longitudinal strain (GLS), global circumferential strain (GCS), and global radial strain (GRS)—were measured and compared across groups. The multivariable regression model was used to identify independent risk factors for VA.ResultsCompared with controls, HTN patients showed significantly elevated LV mass index (LVMI) and maximal wall thickness (LVMWT) (P < 0.05). Both HTN subgroups (with/without LVH) exhibited impaired LV strain parameters (GLS, GCS, GRS) compared to controls (all P < 0.05). Systolic blood pressure (SBP), diastolic blood pressure (DBP), LVMI, and LVMWT correlated significantly with GRS, GCS, and GLS (P < 0.05), with LVMI demonstrating the strongest correlation with GLS (r = 0.58). Multivariable analysis identified GCS, BSA, and history of multi-drug antihypertensive therapy (Hx Multi-Drug AHT) as essential risk factors for VA in HTN patients. ROC analysis established GCS as the primary imaging predictor, with optimal VA discrimination at −17.005% (AUC = 0.848; sensitivity 69%, specificity 89.8%). The combined model (GCS + Hx Multi-Drug AHT + BSA) achieved superior performance (AUC = 0.923, 95% CI 0.868–0.960; sensitivity 85.71%, specificity 88.89%).ConclusionCMR-FT-derived myocardial strain parameters demonstrate high sensitivity in detecting subclinical LV dysfunction in HTN patients. Furthermore, progressive impairment of GCS may serve as an independent risk factor for VA in this population. These findings provide imaging-based evidence to guide early interventions aimed at mitigating cardiac remodeling and arrhythmia development in HTN.